2015
DOI: 10.4097/kjae.2015.68.5.455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of i-gel® and LMA Supreme® during laparoscopic cholecystectomy

Abstract: BackgroundIn laparoscopic surgical procedures, many clinicians recommend supraglottic airway devices as good alternatives to intubation. We compared the i-gel® (i-gel) and LMA Supreme® (Supreme Laryngeal Mask Airway, SLMA) airway devices during laparoscopic cholecystectomy regarding sealing pressure and respiratory parameters before, during, and after pneumoperitoneum.MethodsFollowing Institutional Review Board approval and written informed consent, 93 patients were randomly allocated into the i-gel (n = 47) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
4
25
1
3
Order By: Relevance
“…There was no statistically significant difference between the two groups (p>0.05) with respect to above. These results are consistent with the findings of Park et al 12 Both groups were compared statistically for baseline hemodynamic parameters like PR, SBP, DBP after immediate insertion of device, 5 min and 10 min after the device. SpO2 and EtCO2 maintained throughout the study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was no statistically significant difference between the two groups (p>0.05) with respect to above. These results are consistent with the findings of Park et al 12 Both groups were compared statistically for baseline hemodynamic parameters like PR, SBP, DBP after immediate insertion of device, 5 min and 10 min after the device. SpO2 and EtCO2 maintained throughout the study.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were made by Park et al and Belena et al 12,16 On contrary Ragazzi et al reported incidence of sore throat was more in SLMA group compared to I-gel. 17 Dysphagia was reported more in SLMA group (8 cases) than I-gel group (1 case) at one hour.…”
Section: Discussionsupporting
confidence: 87%
“…[1314] A number of randomized clinical trials and a meta-analysis also reported that OLP between i-gel™ and LMA-S™ is similar. [678915] On the contrary to our findings, Chew et al . and Ragazzi et al .…”
Section: Discussioncontrasting
confidence: 99%
“…A number of RCTs also reported similar insertion time between LMA-S™ and i-gel™. [81220] Theiler et al . reported that LMA-S™ insertion is significantly shorter in patients with cervical collar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation